(untitled) (Global Journal of Medical Research, 2022)
Abstarct-This study examines the relationship between atherosclerotic lesions of the coronary arteries and quantitative indicators of epicardial adipose tissue according to MSCT data. Overall, 96 patients were investigated who were admitted to the hospital during 2019-2020 years, with a diagnosis and suspicion of coronary artery disease, who were examined and treated at the State Institution Republican Specialized Scientific and Practical Medical Center for Surgery named after Academician V. Vakhidov. Of the 96 patients, there were 51 men and 45 women; the age of all patients was over 45 years old (59.75±0.9 years). Based on the results of MSCT angiography, the patients were classified according to the degree of stenosis using the CAD-RADs system. The thickness, area, and volume of epicardial adipose tissue (EAT) were determined in all patients. A direct correlation of average strength between the volume of EAT and the degree of coronary atherosclerosis (r=0.59) (p